NEUROLEPTIC MALIGNANT SYNDROME: THE NEED FOR A HIGH INDEX OF CLINICAL SUSPICION EVEN WHEN ON ATYPICAL ANTIPSYCHOTICS IN ASIAN POPULATION – A CASE REPORT - HIMA SABU; JAVED ANVAR HUSSAIN; MINU BABY; AISWARYA R NAIR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Neuroleptic malignant syndrome (NMS) is a rare life-threatening neurological disorder associated with the use of antipsychotic medications. Second-generation antipsychotics were assumed to have a lower risk of developing NMS; however, cases are being reported nowadays. Here, we are discussing of a 64-year-old male patient with underlying coronary artery disease, chronic obstructive pulmonary disease, and recurrent depressive disorder for which he was on an atypical antipsychotic, olanzepine from an outside center admitted in our hospital with the syndrome of NMS. He was brought to the emergency department with complaints of delirium, confusion, and urinary incontinence. On examination, he had fever, disorientation, and cogwheel rigidity with raised creatine phosphokinase values in blood tests. He was diagnosed with NMS after ruling out other causes for delirium and similar manifestations such as serotonin syndrome and malignant hyperthermia. This case illustrates the fact that the incidence of NMS due to atypical antipsychotics is not negligible and the need for monitoring elderly patients who take this class of drug, especially while escalating doses as the condition is fatal. Our case report also looks into other probable predisposing as well as precipitating factors which need to be considered with caution.